KONSEP I’TIMANIYA DALAM PANDANGAN TAHA ABDURRAHMAN - Muhammad Iqbal (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2023)
This article aims to examine the ethical concept of I'timaniya according to Taha Abdurrahman. Through his capacity and position as a modern Muslim scientist, Taha tries to open up new ideas using an ethical activity approach (al-akhlâq al-`amaliy) to criticize western modernism. This is the main point of his criticism of the hegemony of western modernist thoughts which are indifferent and deny ethical activities. Due to this anxiety, Taha Abdurrahman tries to bring it back to the core and discusses these two main elements in one full concept, namely forming a new concept based on Islamic ethics.